Sinisa Children's Literacy Program: SWOT Analysis to Increase Reading Interest in Salatiga - Hamudy, Moh Ilham A; Rifki, M Saidi; Hayuningtyas, Mukhlisha (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Early literacy plays a crucial role in building a strong foundation for children's reading and writing skills. In Salatiga, the Library and Archives Office (Dinpersip) initiated the Salatiga Early Literacy Awareness (Sinisa) program to cultivate children's reading interest from an early age. Although the program holds great potential, its implementation remains limited to book provision and does not fully address essential literacy aspects. This study evaluates the effectiveness of the Sinisa program and identifies the factors influencing its success using a descriptive approach and SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). The findings indicate that the program's strengths lie in Dinpersip's active involvement, content relevance to local culture, and community collaboration. However, it faces several weaknesses, including budget limitations, suboptimal content, and the absence of a clear evaluation framework. Opportunities for program development include cross-sector collaboration and increasing literacy awareness, while the primary threats stem from digital media competition and the lack of commitment from the local government. As a novel contribution to early literacy studies, this research recommends implementing a Community-Based Literacy model that actively involves parents and communities to enhance the effectiveness of the Sinisa program. Additionally, strengthening strategic partnerships between Dinpersip, educational institutions, and communities is essential to fostering a conducive environment for sustained reading interest. These measures aim to optimize the Sinisa program in cultivating a literate generation in Salatiga.Â